UTILIZATION OF IDLE REGIONAL ASSETS AND REGIONAL FISCAL PERFORMANCE: AN ANALYSIS VALUE FOR MONEY IN GOVERNMENT NORTH SUMATRA PROVINCE - Sandro Simatupang; Eka Nurmala Sari (PT. Radja Intercontinental Publishing, 2026)
Utilization of Regional Property (BMD) located in in idle condition becomes issue important in management finance areas , especially in the middle demands improvement independence fiscal and optimization source Power public . In many government area , assets area recorded worth big in balance sheet , however Not yet fully utilized For support performance fiscal in a way sustainable research​ This aim For analyze conditions and practices utilization of idle BMD in the Government North Sumatra Province , evaluates its performance based on Value for Money ( VfM ) perspective , as well as study the implications to performance fiscal areas , especially Regional Original Income (PAD) Study This use approach qualitative with design studies case . Data collected through analysis report finance government area , report results Audit Board inspection Finance (BPK), and tracing document relevant policies and publications .​ Research result show that Government North Sumatra Province has portfolio asset large area , but​ Still there are 113 BMD in the form of land as well as buildings and structures in idle condition as listed in the BPK IHPS Semester II 2025. Contribution utilization of BMD for PAD is still relatively small and not yet comparable with potential assets owned . Evaluation based on VfM show that utilization of idle BMD not yet fulfil criteria economical , efficient and effective optimally . This condition influenced by limitations maturity management assets , weaknesses integration utilization asset to in fiscal strategy area . and height caution bureaucracy consequence audit risk . Study This contribute in a way theoretical with integrate public asset management perspective , value for money, and decentralization fiscal in analyze utilization asset area . In terms of empirical , research This enrich literature with proof studies cases at the government level province and offers framework evaluation performance utilization of BMD that is oriented results . Limitations study This lies in the design studies case single and quantitative data limitations related costs and values economy assets . Research furthermore recommended For use mixed methods approach , expanding scope of the study area , as well as develop measurement quantitative For evaluate potential and performance utilization asset area in a way more comprehensive .